Correction to: Authors’ Reply to Letter to the Editor: Continued improvement to genetic diversity indicator for CBD - Linda Laikre; Paul A. Hohenlohe; Fred W. Allendorf; Laura D. Bertola; Martin F. Breed; Michael W. Bruford; W. Chris Funk; Gonzalo Gajardo; Antonio González-Rodríguez; Catherine E. Grueber; Philip W. Hedrick; Myriam Heuertz; et al. (Conservation Genetics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10592-021-01376-9

Authors’ Reply to Letter to the Editor: Continued improvement to genetic diversity indicator for CBD - Linda Laikre; Paul A. Hohenlohe; Fred W. Allendorf; Laura D. Bertola; Martin F. Breed; Michael W. Bruford; W. Chris Funk; Gonzalo Gajardo; Antonio González-Rodríguez; Catherine E. Grueber; Philip W. Hedrick; Myriam Heuertz; et al. (Conservation Genetics, 2021)

Population differentiation and historical demography of the threatened snowy plover Charadrius nivosus (Cassin, 1858) - Josephine D’Urban Jackson; Michael W. Bruford; Tamás Székely; Jeffrey M. DaCosta; Michael D. Sorenson; Isa-Rita M. Russo; Kathryn H. Maher; Medardo Cruz-López; Daniel Galindo-Espinosa; Eduardo Palacios; Atahualpa Eduardo De Sucre-Medrano; John Cavitt; et al. (Conservation Genetics, 2020)
Delineating conservation units is a complex and often controversial process that is particularly challenging for highly vagile species. Here, we reassess population genetic structure and identify those populations of highest conservation value in the threatened snowy plover ( Charadrius nivosus, Cassin, 1858), a partial migrant shorebird endemic to the Americas. We use four categories of genetic data—mitochondrial DNA (mtDNA), microsatellites, Z-linked and autosomal single nucleotide polymorphisms (SNPs)—to: (1) assess subspecies delineation and examine population structure (2) compare the sensitivity of the different types of genetic data to detect spatial genetic patterns, and (3) reconstruct demographic history of the populations analysed. Delineation of two traditionally recognised subspecies was broadly supported by all data. In addition, microsatellite and SNPs but not mtDNA supported the recognition of Caribbean snowy plovers ( C. n. tenuirostris ) and Floridian populations (eastern C. n. nivosus ) as distinct genetic lineage and deme, respectively. Low migration rates estimated from autosomal SNPs ( m < 0.03) reflect a general paucity of exchange between genetic lineages. In contrast, we detected strong unidirectional migration ( m = 0.26) from the western into the eastern nivosus deme. Within western nivosus, we found no genetic differentiation between coastal Pacific and inland populations. The correlation between geographic and genetic distances was weak but significant for all genetic data sets. All demes showed signatures of bottlenecks occurring during the past 1000 years. We conclude that at least four snowy plover conservation units are warranted: in addition to subspecies nivosus and occidentalis, a third unit comprises the Caribbean tenuirostris lineage and a fourth unit the distinct eastern nivosus deme.

Messing about on the river: the role of geographic barriers in shaping the genetic structure of Bornean small mammals in a fragmented landscape - Jennifer Brunke; Ute Radespiel; Isa-Rita Russo; Michael W. Bruford; Benoit Goossens (Conservation Genetics, 2019)

Genetic diversity and cryptic population re-establishment: management implications for the Bojer’s skink (Gongylomorphus bojerii) - Sarah J. du Plessis; Joanna Howard-McCombe; Zoe E. Melvin; Eleanor C. Sheppard; Isa-Rita M. Russo; Rouben Mootoocurpen; Matt Goetz; Richard P. Young; Nik C. Cole; Michael W. Bruford (Conservation Genetics, 2019)

More grist for the mill? Species delimitation in the genomic era and its implications for conservation - David W. G. Stanton; Peter Frandsen; Ryan K. Waples; Rasmus Heller; Isa-Rita M. Russo; Pablo A. Orozco-terWengel; Casper-Emil Tingskov Pedersen; Hans R. Siegismund; Michael W. Bruford (Conservation Genetics, 2019)